1986
DOI: 10.1099/00222615-22-3-209
|View full text |Cite
|
Sign up to set email alerts
|

Phage-typing patterns and lysogenicity of methicillin-resistant strains of Staphylococcus aureus from Sydney, Australia, 1965-85

Abstract: Summary. Methicillin-resistant strains of Staphylococcus aureus isolated at the Royal Prince Alfred Hospital since 1965 were differentiated by phage-typing and by their lysogenic status. Most of these strains were isolated during two periods, 1965-72 and 1976-85. Nearly all of the strains isolated in the first period had one of four phagetyping patterns. Strains with each typing pattern carried two prophages; these eight phages were all different, as characterised by serological grouping and lytic spectrum. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…The many common properties of the early MRSA isolates suggested a common clonal origin (2), although certain features observed in more recent MRSA might indicate otherwise (3,4). More recently, Lacey et al (5) suggested that one isolate with resistance to fewer antibiotics might be the primordial MRSA.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The many common properties of the early MRSA isolates suggested a common clonal origin (2), although certain features observed in more recent MRSA might indicate otherwise (3,4). More recently, Lacey et al (5) suggested that one isolate with resistance to fewer antibiotics might be the primordial MRSA.…”
mentioning
confidence: 94%
“…Many MRSA have proven difficult to type with the international basic set of phages and a number of alternative systems of typing have been evaluated, including experimental phages (4,8) and a variety of DNA or protein electrophoretic techniques (9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…These early MRSA strains as well as subsequent MRSA strains have been preserved in the Staphylococcal Reference Collection at RPAH. Our phage typing data on strains from this collection suggested a population shift might have occurred in the late 1970s (33). We subsequently examined the collection genotypically and provided evidence to suggest that clonal displacement of the then-endemic strains by new strains of MRSA had occurred in this Australian hospital (6).…”
mentioning
confidence: 99%
“…All strains not typable showed weak lysis with the experimental phages 88 and 87M (Vickery et al, 1986).…”
Section: Genetic Relationships Determined By Numerical Analysis Of Jrmentioning
confidence: 96%
“…Accurate identification of MRSA strains or types, and their carriers within a hospital, are of special importance in coping with these outbreaks, and a range of methods designed to do this have been described (Berke & Tilton, 1986 Smith & Berezny, 1986;Vickery et al, 1986).…”
Section: Introductionmentioning
confidence: 99%